2016
DOI: 10.1186/s13033-016-0048-8
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary psychiatric admission: how the patients are detected and the general practitioners’ expectations for hospitalization. An interview-based study

Abstract: BackgroundIn Norway, it is usually GPs that refer patients to involuntary admission. A high proportion of such referrals come from out-of-hours clinics. Little is known about who first initiate the contact between the patients and the referring doctors and which expectations the referring doctors have with respect to the involuntary admissions. The aim of the study was to examine who first detected the patients who were subsequently involuntarily admitted, and to examine the referring doctors’ expectations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Eleven studies [ 26 , 27 , 44 – 52 ] examined the topic of the referral and/or the admission of involuntary patients to psychiatric hospitals. The studies were primarily based on the examination of medical records [ 44 – 48 , 52 ] or on interviews with referring GPs [ 26 , 49 51 ] or admitting specialists [ 27 ]. In this category, two of the 11 studies were qualitative [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies [ 26 , 27 , 44 – 52 ] examined the topic of the referral and/or the admission of involuntary patients to psychiatric hospitals. The studies were primarily based on the examination of medical records [ 44 – 48 , 52 ] or on interviews with referring GPs [ 26 , 49 51 ] or admitting specialists [ 27 ]. In this category, two of the 11 studies were qualitative [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many referring doctors find it difficult to apply the legal criteria [ 49 ] and one study [ 50 ] found that the danger criterion had been used most often. The most frequent expectations for the involuntary admissions are the starting of treatment with neuroleptics and taking care of the patient [ 51 ]. While one study found that referring GPs and admitting specialists were mostly in agreement [ 45 ], other studies had found that 27% [ 52 ], 45% [ 46 ], and 54% [ 44 ] were disallowed, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Methods in implementing psychiatric commitment include consideration of individual's autonomy, and decision-making powers or referrals which may follow mandates that place the power to decide to non-medical authorities such as judges, courts, government officials, or social workers as well as family or significant others and decisions of the mental health professionals according to legal provisions. [6] Bola and col-leagues' study [7] in South Korea revealed that more than half (66%-77%) of involuntary admissions were referred primarily by the family while Rotvold and Wynn [8] accounted 25% in their study. Family involvement in the involuntary admission of the patient may pose long-term consequences in terms of relationship with the patient.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, approximately half of the involuntary admissions had been referred from doctors working at municipal out-of-hours clinics [5]. These doctors often felt pressured to commit patients to psychiatric hospital, as few other options were available at nights and week-ends [5][6][7]. The increased availability of other services at nights and week-ends could therefore possibly result in reduced levels of coercion.…”
mentioning
confidence: 99%